The Words “Menolak” and “Menerima” in Forensic Linguistic Study - Sutarsih Sutarsih; Ade Mulyanah (International Journal of Science and Applied Science: Conference Series, 2022)
The words "menolak" and "menerima" in the Indonesian language have almost the same meaning. In linguistics, it is ordained that every word has a meaning, synonymous words can and cannot replace each other, and words can potentially be legal cases. Therefore,it is necessary to study how to use the two words and the impact caused by their use. Besides, it is important to know why it is required to understand the meaning of both words. To answer the problems, the researchers conduct a forensic linguistic study with descriptive analysis with Systemic Functional Linguistic theory. The data of this research is the use of the two words taken from news texts in the mass media in the network. In this article, the analysis of the use of words is in some fields: health, politics, law, economics, and in culture. The research results for "declining" and "returning" reveal three findings. Firstly, the use of the two words cannot replace each other. Secondly, the impact caused by using the two words is the form and the parties involved. Thirdly, there is a reason for the need to understand the use of the two words. Therefore, no language use cases lead to the realm of law.